ANDROID-BASED TAPIS CRAFT MARKETING STRATEGY AS AN EFFORT TO INCREASE THE EMPOWERMENT OF HOUSEWIVES AND TEENAGERS IN BATURAJA WAYLIMA VILLAGE - Mustika Dewi (International Journal of Artificial Intelligence and Robotic Technology (IJAIRTec), 2022)
Tapis is one of Lampung's traditional products with a special motif pattern of gold and silver threads, the process of making tapis cloth is quite complicated and must be done manually so it takes weeks. This is what makes tapis fabric have a relatively expensive price. In Baturaja Waylima Village, there is still limited and lack of understanding about online marketing. The strategy that will be carried out in increasing production and how to market production in the digital era is by means of several stages of activities, namely including preparation, market surveys, production processes. In doing promotion, several promotional strategies will be carried out, namely with Instagram, Brochure, and other online media. This study aims to describe the marketing strategy of android-based tapis crafts as an effort to increase the empowerment of housewives and teenagers in Baturaja Waylima Village.